Muslims in America survival to success - Wahhaj, Siraj; One Islam Publications; Islamic Society of Central Florida; Mecca Centric Da'wah Group (N.S.W, Australia : One Islam Productions, 2006)
This opening session of the United Muslim Conference in Orlando, Florida deals with the mission statement of the Muslims living in the world today. Imam Siraj draws this statement from the Holy Qur'an and sets the tone for the entire conferenmce by exhorting those attending to be a balanced, just and good nation
Title from title screen
The Mission of Muslim Ummah presents in United Muslim Conference, Orlando, Florida, December 24-26, 1997
Presenter : Siraj Wahhaj
Keywords: Religious life -- Islam; Islam -- Customs and practices